2023
DOI: 10.1007/s11019-023-10163-x
|View full text |Cite
|
Sign up to set email alerts
|

“Green informed consent” in the classroom, clinic, and consultation room

Abstract: The carbon emissions of global health care activities make up 4–5% of total world emissions, placing it on par with the food sector. Carbon emissions are particularly relevant for health care because of climate change health hazards. Doctors and health care professionals must connect their health care delivery with carbon emissions and minimize resource use when possible as a part of their obligation to do no harm. Given that reducing carbon is a global ethical priority, the informed consent process in health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Bringing climate-consciousness into discussions with patients -the notion of "green informed consent" seems especially pertinent where low-carbon treatment alternatives are available. (50) As it happens, research (51) and case studies (52) have demonstrated the public are concerned about the health impacts of climate change, with broad public support for a range of decarbonising measures, including patients willing to change their own behaviours (such as returning unused medications), and responding positively to exploring low-carbon treatments.…”
Section: Autonomymentioning
confidence: 99%
“…Bringing climate-consciousness into discussions with patients -the notion of "green informed consent" seems especially pertinent where low-carbon treatment alternatives are available. (50) As it happens, research (51) and case studies (52) have demonstrated the public are concerned about the health impacts of climate change, with broad public support for a range of decarbonising measures, including patients willing to change their own behaviours (such as returning unused medications), and responding positively to exploring low-carbon treatments.…”
Section: Autonomymentioning
confidence: 99%
“…On the other hand, recent literature increasingly highlights how issues of climate protection are integrated in patient-physician communication, for example, to arrive at a 'Green Informed Consent' which is in line with the patient's preferences and values. 24 Philosophical theories of climate ethics 25 26 may serve as starting points for an analysis for ethical duties of preserving the world wide ecosystem, but do not fully account for the specific social and ethical role of physicians as highly trusted professionals.…”
Section: Climate Change As a Matter Of Physicians' Professional Ethicsmentioning
confidence: 99%